Energieffektivisering av Saint-Gobain AB Sweden Gyprocs torksystem : energy efficiency of Saint-Gobain AB Sweden Gyprocs drying system - von Bergen, Elsa; Christiansen, Linus; Eriksson, Jonathan; Israelsson, Karin; Laurell, Algot; Nedstrand, Emma; Pettersson, Anton; Werre, Albin (SLU/Dept. of Energy and Technology, 2021)
When producing gypsum boards at Saint-Gobain AB Sweden Gyproc an approximatly 200 m long oven is used in a drying process. In this process a lot of energy is wasted as hot flue gas and hot water. When investigating applicable heat recovery systems roughly 1 500 MWh/yr was found possible to reuse in their own facilites. To achieve this two heat exchangers need to be installed as well as insulating an already exsisting heat exchanger. In order to avoid high pressure drops in the heat exchangers an additional fan needs to be implemented. The study is done only on one product that Gyproc delivers, called GNE. To extract highest possible energy from the hot water a plate heat exchanger with water to water flow has been implemented. Since the hot flue gas contains a lot of steam a condenser has been used to fully utilize the latent energy. The results obtained in the study shows that with the suggested solutions Gyproc will use less energy and therefore emitt less CO2.